Trotsky - Thatcher, Ian D. (Routledge, 2003)
Publisher's description: Leon Trotsky has always aroused strong passions-historians love and hate him in equal measure. This new biography provides a full account of his political life, based upon a wealth of primary sources, including previously unpublished material. Ian D. Thatcher paints a new picture of Trotsky's standing in Russian and world history. Key myths about Trotsky's heroic work as a revolutionary, especially in Russia's first revolution of 1905 and the Russian Civil War, are thrown into question. Although Trotsky had a limited understanding of crucial contemporary events such as Hitler's rise to power, he was an important thinker and politician, not least as a trenchant critic of Stalin's version of communism. This study provides a clear and accessible introduction to Trotsky's life and thought for anyone interested in twentieth-century Russian and World History.